Factors Influencing Rail Service Passenger Loyalty Among Older Thai Adults - Ratchaphong Lieophairot; Nuttawut Rojniruttikul; Singha Chaveesuk (Sustainability, 2025)
This study investigates the drivers of older adult loyalty (OAL) in Thailand’s rail passenger transport sector. Using structural equation modeling (SEM), data from 625 older rail passengers were analyzed to examine the direct and indirect pathways shaping loyalty. The results demonstrate that service innovation (SI) exerted the strongest overall effect on OAL, both directly and through its influence on service quality (SQ) and passenger satisfaction (PS). Interaction-oriented innovations and accessible delivery technologies emerged as particularly influential, highlighting the importance of human-centered innovation in aging societies. Perceived value (PV) also significantly predicted SQ, PS, and OAL, with price fairness, emotional reassurance, and reliability as key sub-dimensions. SQ was confirmed as a central mediator, translating SI and PV into satisfaction and loyalty outcomes, while PS, although significant, played a secondary role. The findings extend existing theories by demonstrating that innovation and value outweigh satisfaction as loyalty drivers in this context. They advance the SERVQUAL, Value–Attitude–Behavior, and Expectancy–Disconfirmation frameworks by showing that satisfaction is a necessary but insufficient condition for loyalty. The study emphasizes aligning innovation, value, and quality to build inclusive, sustainable loyalty strategies for older rail passengers.
Keywords: Urban Transport and Accessibility; Older Adults Driving Studies; Transportation and Mobility Innovations